EVALUATION OF READING PARK MANAGEMENT BASED ON THE CIPP MODEL IN INCREASING CHILDREN'S INTEREST IN READING - Syarifudin Yunus; Didik Notosudjono; Martinus Tukiran (Suluh Adiluhung Publisher (SAPub), 2024)
Reading parks play an important role in increasing children's interest in reading. This study aims to measure the effectiveness of reading park management in Bogor Regency, using the CIPP (Context, Input, Process, Product) model qualitatively. The instruments used include document studies, interviews, questionnaires, observations, and focus group discussions. Data analysis is an interactive analysis that is presented in its entirety. The results of the study describe that the evaluation of the context component is classified as good with a score of 4.03, the input component is sufficient - 3.29, the process component is sufficient - 3.40, and the product component is sufficient - 3.55. It is concluded that the evaluation of the management of reading parks in Bogor Regency is classified as